2015
DOI: 10.1590/s0080-623420150000500009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adherence to measures for the prevention of surgical site infections by the surgical team

Abstract: Objective: Evaluate pre-and intraoperative practices adopted by medical and nursing teams for the prevention of surgical infections. Method: A prospective study carried out in the period of April to May 2013, in a surgical center of a university hospital in Belo Horizonte, Minas Gerais. Results: 18 surgeries were followed and 214 surgical gloves were analyzed, of which 23 (10.7%) had postoperative glove perforation detected, with 52.2% being perceived by users. Hair removal was performed on 27.7% of patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
0
11
2
8
Order By: Relevance
“…In contrast to the current study, double gloving was significantly associated with longer duration of operation in a study in Brazil, possibly due to the greater risk of glove perforation with longer duration of operations [15]. It is expected that the need for change of or double gloving in this study is underestimated.…”
Section: Change Of or Double Glovescontrasting
confidence: 95%
See 3 more Smart Citations
“…In contrast to the current study, double gloving was significantly associated with longer duration of operation in a study in Brazil, possibly due to the greater risk of glove perforation with longer duration of operations [15]. It is expected that the need for change of or double gloving in this study is underestimated.…”
Section: Change Of or Double Glovescontrasting
confidence: 95%
“…The WHO guidelines [8] aim to achieve this, but several studies have shown that adherence is not optimal [33][34][35]. In comparison to a Brazilian study [15], this study found a higher rate of administering surgical antibiotic prophylaxis (96.0% vs 77.6%), which was comparable to an Italian study [16] (96.0% vs 96.8%). The effectivity of surgical antibiotic prophylaxis may depend on the type of surgery performed [36], and as a result, if a surgeon is aware of this, the adherence to SSI prevention guidelines might be expected to be improved.…”
Section: Surgical Antibiotic Prophylaxiscontrasting
confidence: 44%
See 2 more Smart Citations
“…Muitos fatores contribuem para o risco dessas infecções, tais como os relacionados ao paciente e à equipe, mas, essencialmente, da possibilidade de contaminação da ferida cirúrgica durante o procedimento operatório, período trans-operatório e, portanto, quanto maior a contaminação microbiana nesse período, maior a chance de infecção por conta da introdução de microrganismos na cavidade cirúrgica aberta e manipulada 6,7 .…”
Section: Introductionunclassified